ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN LABA BANK SYARIAH DI INDONESIA PERIODE 2005-2020 - Susi Melinasari (ALAMIAH : Jurnal Muamalah dan Ekonomi Syariah, 2023)
This study analyzes the effect of Capital Adequacy Ratio (CAR), Return on Assets (ROA), Non Performing Finance (NPF), Finance to Deposit Ratio (FDR) and Operating Expenses on Operating Income (BOPO) on Profit Growth of Islamic Banks in Indonesia. The data used in this study is secondary data taken annually during the period 2005-2020. The sampling technique used in this research is purposive sampling. The data analysis method used in this study is panel data regression analysis using the Microsoft Excel 2013 SPSS version 25 computer program. The results in this study indicate that CAR, ROA, NPF, FDR and BOPO simultaneously have a significant effect on the Profit Growth of Islamic Banks. CAR and FDR partially have no significant effect on Profit Growth of Islamic Banks while ROA, NPF and BOPO partially have a significant effect on Profit Growth of Islamic Banks in Indonesia.